La Gestión Financiera y su incidencia en la Ejecución Presupuestaria del GAD Municipal del Cantón Alausí, durante el período 2019-2020. - Caiza Parco, Willian Patricio (2022)
This research started with the objective of evaluating the financial management and its impact on the budget execution of the Municipal GAD of the Alausí canton, during the 2019-2020 period. The different methods, techniques and research instruments for data collection were determined, in order to diagnose financial management and establish the level of budget execution in the study institution, compared to what was planned. Therefore, it was necessary to survey the processes in the financial management area and the vertical and horizontal analysis of the financial statements, to subsequently apply financial management indicators for. It was concluded that the entity failed to collect the income (-29%- Year 2019; Year -20%- Year 2020) established since its inception, due to non-compliance with Capital and Financing income, with a level of execution compliance 48% in 2019 and 46% in 2020, as scheduled. It is recommended to apply the evaluation and monitoring stages, as part of the administrative process, for a correct execution of the budget and the articulation of the areas to carry out corrective actions on time and to be able to deliver results according to what was programmed, thus achieving, measure the level of compliance based on what was planned in terms of efficiency, effectiveness and economy.